MUSYRIFAH’S EFFORTS IN HANDLING IMPACT OF ANXIETY ABOUT SELF-ADJUSMENT IN CLASS STUDENT REGULER TMI AL-AMIEN PRENDUAN - siti Khotijah; Malihatul Mahfudhoh; Uswatun Hasanah (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2023)
In this study it was found that some class one regular female students who incidentally have not been able to adjust to the new environment often experience fear, anxiety, worry in their daily activities. As for these symptoms can hinder the daily activities of female students. So that musyrifah efforts are needed because musyrifah has an important role and authority in every problem and problem of the child under her guidance, especially in the dormitory. To find out more about how musyrifah efforts. So, the researcher used a qualitative research approach with case studies. As for data collection techniques researchers use interviews, observation and documentation. From this technique, then researchers process and analyze to obtain data or information. The subjects of this research were Musyrifah, Mulahidzoh, and female students of Maya's room. The results of the research obtained were the fact that musyrifah had efforts to deal with anxiety about self-adjustment in regular first grade female students, including: First: Strengthening musyrifah's emotional relationship with female students, are; Controlling, giving sympathy. Second, Be a model for female students; Providing role models, collaborating with superiors (mutsakifah or Nyai). Third, mental strengthening; Giving advice, motivating, guiding. The supporting and inhibiting factors for musyrifah in dealing with anxiety about adjustment in the class one female students of TMI Al-Amien Prenduan include: a. Supporting factors; There is cooperation or collaboration with the homeroom teacher or room mutsakifah, There is openness from the students, A sense of responsibility. And obstacle factor; Insufficient time intensity, Less effort from students